Redesign User Interface Dan User Experience Pada Website Eclinic Menggunakan Metode Design Thinking - Khaeva Hasna; Meriska Defriani; Moch Hafid Totohendarto (STMIK Budi Darma, 2023)
Since 2022 Munjul Jaya Clinic Purwakarta has collaborated with PT. Infokes Indonesia to start making applicationseClinic web-based in order to improve clinical services. Inappropriate user interaction causes a lot of confusion among userswebsite the. After doingusability testing with users,user interface which now feels like it doesn't provide a good experience, because it makes users confused. In the observation results obtained several features that make it difficult touser perform services including, design and placement of menus less attractive to users, usagecopywriting which is not quite right, and it is difficult to identify the title of a content, so that users find it difficult to provide services. In this study researchers used the methodDesign Thinking for researchers to seek to understand users, challenge assumptions, and redefine problems in creating strategies and alternative solutions that may not be immediately apparent at the early description level. At the stage of testing the resultsprototype This will be done using the method test methodSingle Ease Questionnaire (SEQ) which has an assessment score of 1-7, and the result of the SEQ score is worth 5.5 a task is said to be difficult if the task's value is below number 5. Test resultsprototype which was carried out with 10 respondents to get an average score of 6.4 which meanswebsite it's easy to use